2012
DOI: 10.1088/0031-9155/57/13/4353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel triple-channel radiochromic film analysis procedure using EBT2

Abstract: A novel approach to read out radiochromic film was introduced recently by the manufacturer of GafChromic film. In this study, the performance of this triple-channel film dosimetry method was compared against the conventional single-red-channel film dosimetry procedure, with and without inclusion of a pre-irradiation (pre-IR) film scan, using EBT2 film and kilo- and megavoltage photon beams up to 10 Gy. When considering regions of interest averaged doses, the triple-channel method and both single-channel method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 22 publications
0
52
0
Order By: Relevance
“…Such information can be exploited to correct the nonuniformity error 13 , 14 . In addition, by combining the X‐ray double‐exposure technique before true irradiation with the red‐channel information, scans increase once; however, the nonuniformity reduction is not improved from that of multichannel analysis (15) . The X‐rays of the double‐exposure technique can be replaced by density increases in Gafchromic films irradiated with ultraviolet (UV) rays (16) …”
Section: Introductionmentioning
confidence: 99%
“…Such information can be exploited to correct the nonuniformity error 13 , 14 . In addition, by combining the X‐ray double‐exposure technique before true irradiation with the red‐channel information, scans increase once; however, the nonuniformity reduction is not improved from that of multichannel analysis (15) . The X‐rays of the double‐exposure technique can be replaced by density increases in Gafchromic films irradiated with ultraviolet (UV) rays (16) …”
Section: Introductionmentioning
confidence: 99%
“…Radiation dose information is provided by a red channel, and information on the degree of uniformity is provided by a blue channel, which information is used for nonuniformity corrections 16 , 17 . However, the uniformity of Gafchromic EBT2 in a single red channel using a double exposure technique (pre‐exposure technique) was equal to that of a triple‐channel method (8) . Therefore, thickness‐unevenness of the active layer was enhanced by uniformly irradiating with UV rays, such as UV exposure to Gafchromic EBT film (7) …”
Section: Discussionmentioning
confidence: 99%
“…In these films, a yellow dye is included in an active layer to reduce nonuniformity errors. A study has shown that the uniformity of Gafchromic EBT2 with a single red channel in a double‐exposure technique (pre‐irradiation technique) is equal to that of a triple‐channel method (8) . Thus, UV could be used for pre‐exposure to improve uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the gamma pass rates with a DD of 3% and DTA of 3 mm were over 95% for all plans. Van Hoof et al (15) assessed the multichannel method using EBT2 film and reported that the dose discrepancies from the TPS were small, in the order of 0 to 5 cGy for a single square beam. Hayashi et al (14) also performed a similar assessment and reported that the average gamma pass rates in the IMRT and VMAT dose verification were 97.2%±0.8%.…”
Section: Discussionmentioning
confidence: 99%
“…This method allows the separation of the dose‐dependent and dose‐independent parts of the scanned signal, and the multichannel method shows a significant improvement in spatial homogeneity. Hayashi et al (14) and Van Hoof et al (15) reported on the usefulness of the multichannel method compared to the single‐channel method. Moreover, Pevez Azorin et al (16) developed an improved multichannel method by considering the information on unirradiated film.…”
Section: Introductionmentioning
confidence: 99%